2021
DOI: 10.3389/fpsyt.2020.616829
|View full text |Cite
|
Sign up to set email alerts
|

Brief Research Report: A Pilot Study of Cognitive Behavioral Regulation Therapy (CBT-REG) for Young People at High Risk of Early Transition to Bipolar Disorders

Abstract: Attempts to increase early identification of individuals in the early stages of bipolar disorders (i.e., individuals at high risk of bipolar disorders and/or experiencing a subthreshold syndrome with bipolar symptoms) have highlighted the need to develop high benefit-low risk interventions. We suggest that any new psychological therapy should (i) be acceptable to young people seeking help for the first time, (ii) be applicable to “at risk” conditions and sub-syndromal states and (iii) consider pluripotent fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 31 publications
(65 reference statements)
0
1
0
Order By: Relevance
“… 68 Recent studies have begun to show the results of cognitive behavioral therapy (CBT) for ER. 69 , 70 Yang et al 69 investigated the efficacy of 12 weeks of Mindfulness-Based Cognitive Therapy for Children (MBCT-C) on structural brain networks for mood-dysregulated youth with familial risk for BD and found that, after MBCT-C, disrupted topological properties in the mood-dysregulated group were significantly reduced. A pilot study by Scott & Meyer 70 investigated the effects of Cognitive Behavioral Regulation Therapy (CBT-REG) for young people at high risk of PBD, with outcome data indicating that the intervention appears to demonstrate a relatively high benefit-to-risk ratio.…”
Section: Discussionmentioning
confidence: 99%
“… 68 Recent studies have begun to show the results of cognitive behavioral therapy (CBT) for ER. 69 , 70 Yang et al 69 investigated the efficacy of 12 weeks of Mindfulness-Based Cognitive Therapy for Children (MBCT-C) on structural brain networks for mood-dysregulated youth with familial risk for BD and found that, after MBCT-C, disrupted topological properties in the mood-dysregulated group were significantly reduced. A pilot study by Scott & Meyer 70 investigated the effects of Cognitive Behavioral Regulation Therapy (CBT-REG) for young people at high risk of PBD, with outcome data indicating that the intervention appears to demonstrate a relatively high benefit-to-risk ratio.…”
Section: Discussionmentioning
confidence: 99%